Management and population fluctuation of cassava mealybug Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) - Gazola, Diego; Pietrowski, Vanda; Zucareli, Claudemir; Barilli, Diandro Ricardo [UNESP]; Ringenberg, Rudiney (Universidade Estadual de Londrina, 2019)
Cassava is one of the main food species for low-income populations, playing a key role in the diet of several communities. In the Central-Southern region of Brazil, several pests are associated with cassava, among which the cassava mealybug stands out due to its high potential for damage. The aim of the present study was to evaluate the population dynamics and the effect of pruning and different cassava management on the developmental stages of mealybug, Phenacoccus. manihoti. The experiment was conducted in Santa Monica, PR, with ‘Cauiá’ cultivar, involving a randomized complete block design with four replications and six treatments: 1) No pruning: intact plants, 2) Pruning soil: pruned close to the soil without plant material, 3) Pruning at 15 cm: conventional pruning at 15 cm of the soil with vegetative material, 4) Pruning + branches: conventional pruning, with the middle portion of the plant in the plot and removal of the apical region of the plant, 5) Pruning + apical: conventional pruning, with the removal of the middle portion of the plant and retaining the apical parts of the plant, and 6) Pruning - branches - apical: conventional pruning, with the removal of the middle and apical portions of the plant. After 7-days of pruning, the number of eggs, nymphs, and adults were counted, and the population variation was monitored at weekly interval for a month. For the insect count, four sites were randomly chosen in a zigzag manner within each plot and four plants were evaluated, totaling 16 plants per plot. Based on the counts, the percentage of plants with eggs, nymphs, and adults was calculated. The data of the variables were transformed by (x+0.5), subjected to analysis of variance and Scott Knot test (5%). The percentage of plants with egg mass and adults of P. manihoti was highest in plots that had no pruning. The pruning close to the soil combined with the removal of vegetative material resulted in plants with fewest eggs of P. manihoti. Removal of the apical region portion of the cassava plant reduced the number of P. manihoti nymphs and adults.
Keywords: Cultural management; Infestation; Insect pest; Manihot esculenta